2016
DOI: 10.3390/nu8100653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proton Pump Inhibitor Administration and Intake of a Combination of Yogurt and Galactooligosaccharides on Bone and Mineral Metabolism in Rats

Abstract: The aim of this study was to investigate the effects of proton pump inhibitor (PPI), the most potent acid-suppressing drug, administration and intake of a combination of yogurt and galactooligosaccharides (YG) on bone and mineral metabolism in adult rats. Twelve-week-old male Wistar rats were divided into three groups: a control group fed the control diet with vehicle administration, a PPI group fed the control diet with PPI administration and a YG + PPI group fed the YG diet with PPI administration. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, the results of the effects of PPIs on calcium absorption are inconsistent [17][18][19]. Besides their effects on calcium, IPP might also affect phosphorus as a rat study indicated that PPI administration influenced phosphorus metabolism via a higher phosphorus absorption [20].…”
Section: Overall Biological Plausibility For the Association Between ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of the effects of PPIs on calcium absorption are inconsistent [17][18][19]. Besides their effects on calcium, IPP might also affect phosphorus as a rat study indicated that PPI administration influenced phosphorus metabolism via a higher phosphorus absorption [20].…”
Section: Overall Biological Plausibility For the Association Between ...mentioning
confidence: 99%
“…Other interaction between the effects of PPI and diet have been evidenced in rats [20,21]. In vitro studies have shown that PPIs, namely omeprazole, inhibited bone resorption [22,23] via selective inhibition of osteoclasts vacuolar H + -ATPase [24].…”
Section: Overall Biological Plausibility For the Association Between ...mentioning
confidence: 99%
“…8 Others have demonstrated a significant decline in bone mineral density, increased bone resorption and decreased bone formation in rats treated with omeprazole for a few months. [9][10][11] However, these models are not perfect as the animals are not infected with H. pylori. Besides, the data on short-term skeletal effects of triple therapy or PPI are very limited.…”
Section: Introductionmentioning
confidence: 99%